Internal Migration. Challenges and Perspectives for the Research Infrastructure - Andreas Farwick (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Research on internal migration covers a wide range of issues with regard to the reasons, distance and direction of moves as well as the process of decision-making. Given the rich field of relevant research objectives and the substantial developments in migration theory it is apparent that the availability of a broad set of data including detailed information on various aspects of life is one of the key factors for ongoing progress in the analysis of internal migration development. Available official aggregated data are useful for descriptive structural analyses. But they are very limited in explaining causal relations. The same holds for cross-sectional data. Some of the described longitudinal data sets consist of retrospective collected event history data that are not suitable for collecting essential information about attitudes and psychological states of the respondents over time. Several prospective longitudinal survey data do not represent essential aspects of internal migration. Data should at least include information on the place of residence (on the smallest possible spatial level), typologies about the characteristics of the place of residence, change of residence, reasons of a move, intentions to move, the dwelling and the neighbourhood as well as on commuting.
Keywords: 330; internal migration; regional migration; migration theory; official data; cross-sectional data; longitudinal data.